2000
DOI: 10.1103/physrevlett.84.1862
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Coulomb Interaction in8BBreakup at Sub-Coulomb Energies

Abstract: The angular distribution for the breakup of 8B-->7Be+p on a 58Ni target has been measured at an incident energy of 25.75 MeV. The data are inconsistent with first-order theories but are remarkably well described by calculations including higher-order effects. The comparison with theory illustrates the importance of the inclusion of the exotic proton halo structure of 8B in accounting for the data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 19 publications
2
83
1
Order By: Relevance
“…They analyzed data from the 6 He + 208 Pb reaction at 22 MeV [18] and the 8 B + 58 Ni reaction at 26 MeV [38]. The 8 B data were equally-well represented in both schemes, but the 6 He data were in much-better agreement with the TC calculation, indicating that the α-particles emitted at backward angles arise from 2n-transfer to slightly-unbound states of the target.…”
Section: Effect Of Breakup On Elastic Scattering and Fusion Near The mentioning
confidence: 99%
“…They analyzed data from the 6 He + 208 Pb reaction at 22 MeV [18] and the 8 B + 58 Ni reaction at 26 MeV [38]. The 8 B data were equally-well represented in both schemes, but the 6 He data were in much-better agreement with the TC calculation, indicating that the α-particles emitted at backward angles arise from 2n-transfer to slightly-unbound states of the target.…”
Section: Effect Of Breakup On Elastic Scattering and Fusion Near The mentioning
confidence: 99%
“…MeV [10,11]. Detailed CDCC calculations by Tostevin et al [4] reproduced the breakup data for both the angular distributions of the 7 Be fragments and their energy distributions measured at several laboratory angles.…”
Section: The 8 B + 58 Ni Experimentsmentioning
confidence: 82%
“…An angular distribution for 7 Be from bu reactions in 8 B + 58 Ni was reported in Refs. [10,11] for E lab = 25.75 MeV. Single-angle (θ = ± 45 • ) measurements for the additional energies of 25.0, 26.9, and 28.4 MeV have also been reported [15].…”
Section: Absolute Normalization Of Datamentioning
confidence: 99%
“…In Ref. [33], an angular distribution for the breakup of 8 B on a 58 Ni target was measured for a near barrier energy. It was found that Coulomb-nuclear interference at very large distances still plays an important role, thus providing evidence for the proton-halo nature of 8 B.…”
Section: Proton-halo Effectsmentioning
confidence: 99%